Revitalization at TMII Papua Pavilion in the face of G20 2022 - Pradini, Gagih; Kusumaningrum, Anisa Putri; Agustiani, Fitri; Hisyam, Aushaf; Wardani, Dyah Mustika (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
The revitalization of the Papua Pavilion at Taman Mini Indonesia Indah (TMII) in anticipation of the G20 summit plays a crucial role in facing international relations challenges. The objective of this revitalization is to enhance the appearance and facilities of the Papua Pavilion, making it more appealing and representative of a unique cultural tourism destination in Indonesia. This research adopts a qualitative approach to comprehend phenomena that do not require quantification. The results of the revitalization efforts demonstrate that the Papua Pavilion has become a prime attraction at TMII, attracting numerous visitors from both domestic and international regions. Updated Standard Operating Procedures (SOP) have been implemented for receiving foreign dignitaries, ensuring improved service and enhancing visitors' experiences. The revitalization of the Papua Pavilion is pivotal in bolstering Papua's position and role in the context of international relations, as well as elevating Papua's branding and image as an enticing investment and tourism destination. To successfully face the G20 summit, strong commitment from the Papua government and active participation from the local community is essential, alongside cooperation among stakeholders.